2007
DOI: 10.3758/bf03192839
|View full text |Cite
|
Sign up to set email alerts
|

Methodological considerations in performing semantic- and translation-priming experiments across languages

Abstract: Research in the field of bilingualism has had as its principal aim to describe the structure and function of memory for bilingual speakers. A primary technique that has been used to examine bilingual memory is an examination of cross-language word priming (semantic and translation), using the lexical decision and pronunciation tasks. Although studies have, on occasion, revealed greater degrees of word priming from a dominant to a subordinate language, in comparison with the reverse, a careful review of the met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
78
1
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 116 publications
(83 citation statements)
references
References 57 publications
(130 reference statements)
3
78
1
1
Order By: Relevance
“…The study also introduced a procedure that tested the TLP effect in bilingual memory. Previously mentioned cross-language studies use translation (review in Altarriba and Basnight-Brown, 2007) and semantic (review in Kroll and Tokowicz, 2005) priming paradigms, which assessed relatedness between words in bilinguals’ different languages. The TLP test introduces a paradigm aiming at assessing relatedness between words in the same language through bilinguals’ other language.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study also introduced a procedure that tested the TLP effect in bilingual memory. Previously mentioned cross-language studies use translation (review in Altarriba and Basnight-Brown, 2007) and semantic (review in Kroll and Tokowicz, 2005) priming paradigms, which assessed relatedness between words in bilinguals’ different languages. The TLP test introduces a paradigm aiming at assessing relatedness between words in the same language through bilinguals’ other language.…”
Section: Resultsmentioning
confidence: 99%
“…The model assumes that words in both languages are directly connected to the underlying concepts and that these language systems are linked through the shared conceptual representations. The cross-language studies using translation priming paradigms (see Altarriba and Basnight-Brown, 2007, for a review) support this assumption by demonstrating that automatic spreading activation takes place between translation equivalents. Figure 3 presents this connection as L1a–TRANS–L2a, where TRANS presents shared conceptual representation of L1 and L2 translation equivalents.…”
Section: Introductionmentioning
confidence: 92%
“…Even if semantic contents of translation equivalents in two languages are not necessarily entirely congruent with each other, an activated lexical unit in one language does spread activation to the other language's mental lexicon as well. One of the most convincing arguments in favor of this strong representational bond between lexica came from crosslinguistic priming studies in a number of (speech-speech) bilingual groups (for recent reviews see Altarriba & Basnight-Brown, 2007). Thus, it seems feasible that speech and sign language also interact with each other during processing and/or share a number of processing mechanisms.…”
Section: Introduction Backgroundmentioning
confidence: 98%
“…Several studies have provided narrative reviews of the asymmetric translation priming effects reported with unbalanced bilinguals in the literature (e.g., Altarriba & Basnight-Brown, 2007; Dimitropoulou et al, 2011; Nakayama et al, 2016; Xia & Andrews, 2015). As summarized in Dimitropoulou et al (2011), only 8 out of 21 experiments reported significant L2–L1 translation priming (mean priming effect: 9 ms, ranging from –6 to 26 ms).…”
Section: Introductionmentioning
confidence: 99%